2018
DOI: 10.1111/ijac.13053
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of alumina‐based ceramic core materials in caustic alkali solutions

Abstract: Corrosion behaviors of the porous alumina‐based ceramic core materials in KOH and NaOH solution were investigated. Corrosion tests were carried out at 100°C, 150°C, and 200°C, and the concentration of KOH and NaOH was 50, 67, and 75 wt%, respectively. The results indicated that the optimal concentration was 67 wt% for KOH solution and 50 wt% for NaOH solution, respectively. Increasing corrosion temperature and prolonging corrosion time were helpful to enhance the corrosion effect, and temperature played an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Actually, it was the SiO 2 in the glass phase that hardly reacted with HNO 3 . In line with Gao et al [20], the Gibbs free energy between Al 2 O 3 and H + obtained from the Microsoft "HSC Chemistry 6" was equal to −112 KJ•mol −1 while that of Al 2 O 3 and OH − was equal to −10.56 KJ•mol −1 . However, the SiO 2 value contained in the glass phase was higher than the Al 2 O 3 value, due to the relatively low dissolution and diffusion rates of the coarse alumina.…”
Section: Chemical Resistancesupporting
confidence: 83%
“…Actually, it was the SiO 2 in the glass phase that hardly reacted with HNO 3 . In line with Gao et al [20], the Gibbs free energy between Al 2 O 3 and H + obtained from the Microsoft "HSC Chemistry 6" was equal to −112 KJ•mol −1 while that of Al 2 O 3 and OH − was equal to −10.56 KJ•mol −1 . However, the SiO 2 value contained in the glass phase was higher than the Al 2 O 3 value, due to the relatively low dissolution and diffusion rates of the coarse alumina.…”
Section: Chemical Resistancesupporting
confidence: 83%
“…Figure 3a,b shows the mass loss of the porous ceramic supports corroded in acidic and alkaline solutions for different times at 80 C in oil bath. It is shown that the mass loss of the samples increased rapidly at the first stage, but changed quite slowly after 12 h, and almost turned into a constant for the 87.2/12.8 sample that corroded in 10 wt% NaOH solution for more than 20 h. Moreover, the mass loss was merely 0.35 wt% for all the ), [10] the SiO 2 content contained in the glass phase was higher than the Al 2 O 3 content, due to the relatively low dissolution and diffusion rates of the coarse alumina. That is to say, the reaction between SiO 2 and OH À (Gibbs free energy: À1075 KJ mol À1 ) was dominant, so the mass loss was lower in H 2 SO 4 than in NaOH.…”
Section: Resultsmentioning
confidence: 91%
“…Actually, it was the SiO 2 in the glass phase that hardly reacted with H 2 SO 4 . Although the Gibbs free energy between Al 2 O 3 and H + (–112 KJ mol −1 , obtained from the Microsoft “HSC Chemistry 6”) is less negative than that between Al 2 O 3 and OH − (–10.56 KJ mol −1 ), the SiO 2 content contained in the glass phase was higher than the Al 2 O 3 content, due to the relatively low dissolution and diffusion rates of the coarse alumina. That is to say, the reaction between SiO 2 and OH − (Gibbs free energy: −1075 KJ mol −1 ) was dominant, so the mass loss was lower in H 2 SO 4 than in NaOH.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ceramics are one such class of materials which have been researched extensively for total hip prosthesis applications due to their high scratch and wear resistance and low friction . However, a new class of materials called nanocrystalline ceramics is being developed by reducing grain sizes and are evaluated for improvement in their mechanical properties . However, there are counterclaims in the literature contradicting these observations …”
Section: Introductionmentioning
confidence: 99%